Studies of thermal annealing and dope composition on the enhancement of separation performance cellulose acetate membrane for brackish water treatment from Jepara - Tutuk Djoko Kusworo; Budiyono Budiyono; U. N. A. Rochyani; E. Sofiana (Diponegoro University, 2014)
Membrane is an alternative technology of water treatment with filtration principle that is being widely developed and used for water treatment. The main objective of this study was to make an asymmetric membrane using cellulose acetate polymer and study the effect of additive and annealing treatment on the morphology structure and performance of cellulose acetate membranes in brackish water treatment. Asymmetric membranes for brackish water treatment were casted using a casting machine process from dope solutions containing cellulose acetates and acetone as a solvent. Membranes was prepared by phase inversion method with variation of polyethylene glycol (PEG) concentration of 1 and 5 wt% and with thermal annealing at 60 oC in 10 seconds and without thermal annealing behavior. Membrane characterization consists of calculation of membrane flux and rejection with brackish water as a feed from Jepara. The research concluded that asymmetric cellulose acetate membrane can be made by dry/wet phase inversion method. The more added concentration of PEG will be resulted the larger pore of membrane. Meanwhile the higher temperature and the longer time of annealing treatment, the skin layer of membrane become denser. Membrane with the composition of 18 wt% cellulose acetate, 5 wt% PEG, 1 wt% distilled water, with heat treatment at temperature of 60 oC for 10 seconds is obtained optimal performance.